Comprehensive phenotypic analysis of the Dp1Tyb mouse strain reveals a broad range of Down syndrome-related phenotypes - Eva Lana-Elola; Heather Cater; Sheona Watson-Scales; Simon Greenaway; Jennifer Müller-Winkler; Dorota Gibbins; Mihaela Nemes; Amy Slender; Tertius Hough; Piia Keskivali-Bond; Cheryl L. Scudamore; Eleanor Herbert; et al. (The Company of Biologists, 2021)
Down syndrome (DS), trisomy 21, results in many complex phenotypes including cognitive deficits, heart defects and craniofacial alterations. Phenotypes arise from an extra copy of human chromosome 21 (Hsa21) genes. However, these dosage-sensitive causative genes remain unknown. Animal models enable identification of genes and pathological mechanisms. The Dp1Tyb mouse model of DS has an extra copy of 63% of Hsa21-orthologous mouse genes. In order to establish whether this model recapitulates DS phenotypes, we comprehensively phenotyped Dp1Tyb mice using 28 tests of different physiological systems and found that 468 out of 1800 parameters were significantly altered. We show that Dp1Tyb mice have wide-ranging DS-like phenotypes, including aberrant erythropoiesis and megakaryopoiesis, reduced bone density, craniofacial changes, altered cardiac function, a pre-diabetic state, and deficits in memory, locomotion, hearing and sleep. Thus, Dp1Tyb mice are an excellent model for investigating complex DS phenotype-genotype relationships for this common disorder.